The role of the Pentahelix model in village development towards sustainable tourism villages in Indonesia: A systematic review - Florianus Pruda Muda (Privietlab, 2026)
Sustainable tourism village development requires effective cross-sector collaboration to balance economic growth, social inclusion, and environmental sustainability. However, existing studies have largely treated the Pentahelix model, which involves the government, academia, business, community, and media, as a normative framework, with limited systematic analysis of its governance dynamics, power relations, and inclusivity outcomes. This study addresses this gap by employing a PRISMA-based Systematic Literature Review of 40 empirical articles published between 2014 and 2025, sourced from Scopus, Web of Science, SINTA, Garuda, and Google Scholar. The findings indicate that multi-actor collaboration under the Pentahelix model contributes to innovation, capacity building, and the preservation of cultural and environmental resources, resulting in improved household income, employment opportunities, and the growth of micro and small enterprises. Nevertheless, the effectiveness of the model remains uneven across contexts due to challenges such as asymmetrical power relations, fragmented coordination, limited funding, and gaps in community capacity, particularly in digital literacy and tourism management. This study contributes to the literature by reconceptualizing the Pentahelix model as a dynamic form of collaborative governance shaped by interaction patterns, institutional arrangements, and inclusivity challenges, rather than a static and idealized framework. The findings emphasize that the success of multi-stakeholder collaboration depends not only on actor involvement but also on the quality of coordination and governance mechanisms. Practically, the study highlights the importance of institutionalized coordination platforms, participatory governance, and targeted capacity-building initiatives. From a policy perspective, it underscores the need for adaptive and inclusive governance strategies in Indonesia, including decentralized collaboration structures and the active inclusion of vulnerable groups. Future research should employ quantitative and mixed-method approaches to examine causal relationships and conduct comparative studies across different contexts.